Library and information center management - Stueart, Robert D; Moran, Barbara B.; Morner, Claudia J. (Santa Barbara, California Libraries Unlimited, 2013)
"This updated edition of the renowned library management textbook provides a comprehensive overview of the techniques needed to effectively manage a contemporary library or information center"--Provided by publisher
First through third editions, published 1977-1987, have title Library management; Fourth through seventh editions, authored by Robert D. Stueart and Barbara B. Moran and published 1993-2007, have title Library and information center management
Includes bibliographical references and index
Keywords: Library administration; Library administration -- United States; Information services -- Management; Information services -- United States -- Management; Electronic books